PROTECTING THE ENVIRONMENT AROUND POLISH QUARRIES FROM HARMFUL SEISMIC VIBRATIONS CAUSED BY ROCK BLASTING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The paper presents the legal and scientific conditions for Polish researchers to determine the vibration velocity and the radius of the safe zone of seismic vibrations generated during rock blasting. Until now, in Poland and worldwide, it has been assumed that seismic vibrations generated during rock blasting with explosives [BM] propagate circularly with equal energy in each direction. However, this is not always the case. A theoretical analysis of the variation of the tangential magnitude Vy of the vibration velocity as a function of the change of the direction angle was carried out for a circular distribution of the vibration velocity. It was shown that the value of the vibration velocity component at the same distance from the vibration source depends on the directional angle between the line of the blast holes and the line connecting the centre of the surface of the excavated BM block and the measuring point. New relationships have been given that take into account the directional angle in the calculation of the maximum values of vibration velocity necessary for the determination of the resulting damage in the building from the SWD. A dynamic impact scale [SWD] for the assessment of building damage as the vibration velocity acting on the building increases is given and discussed. Vibration velocity diagrams measured during the excavation of BM rock have been presented for circular distributions in accordance with theoretical predictions. A vibration velocity diagram for an elliptical distribution, inconsistent with a circular distribution, measured during the excavation of BM rock is presented. It is shown that the directionality of the horizontal tangential component of the vibration velocity exists for both circular and elliptical distribution of vibration velocity in rock excavation with explosive BM. The technical safety of the building in the area of seismic vibrations is determined by the vibration velocity included in zone II of the scale of dynamic influences [SWD] Fig.6A ,6B.